Surgical Correction of Aortic Coarctation with Left Subclavian Artery and Proximal Descending Thoracic Aorta Aneurysm with moderate Left Ventricular Dysfunction in an adult Female- a case report - Gupta, Saikat Das; Haque, Mozibul; Roy, Jagodananda; Mandol, Bhabesh C; Uddin, Mesbah; Chanda, PK (Journal of Bangladesh College of Physicians and Surgeons, 2022)
In its simplest form, coarctation of the aorta (CoA) refers to congenital narrowing of the thoracic aorta. Usually, a significant pressure gradient between the arms and legs is suggestive of the diagnosis. With the advancement of aortic imaging in our country many CoA patients are diagnosed at an adult age, but the management still carries a challenge. We reported a case of 30-year-old lady with CoA with an aortic aneurysm involving proximal left subclavian artery with proximal DTA and LV dysfunction. J Bangladesh Coll Phys Surg 2023; 41: 93-97